Feline idiopathic cystitis: Case Report (Revista Sistemas de Producción Agroecológicos, 2025)
Feline idiopathic cystitis (FIC) is the most common uropathy among feline lower urinary tract diseases (FLUTD). It is a condition of unknown etiology that affects multiple systems in addition to the urinary tract. This report describes the case of a 5-year-old neutered male cat referred to the Veterinary Clinical Center of the Universidad de los Llanos. The patient presented with red urine and abdominal pain, along with a history of urinary obstruction, and was admitted with a previously placed urinary catheter from another veterinary clinic. Hematuria (blood in urine), pain upon palpation of the caudal abdomen, distended bladder (bladder pletora). Complete blood count (CBC) and creatinine levels were within normal ranges. A urinalysis was performed using a sample collected via the urinary catheter. Abdominal ultrasound revealed: Anechoic content in the urinary bladder (consistent with urine). Renal cortical hyperechogenicity and a 1:1 cortex-to-medulla ratio in the renal parenchyma. Continuous maintenance fluid therapy. Tramadol (analgesic). Meloxicam (NSAID for inflammation/pain). Omeprazole (to protect the gastric mucosa). The treatment was adjusted based on the patient's clinical progression. All feline patients with lower urinary tract diseases require specialized medical evaluation that includes not only pharmacological treatment but also a detailed assessment of the patient's environmental and behavioral components to determine the degree of stress and anxiety that may be linked to the diagnosis.
Keywords: Dysuria; Pandora's syndrome; Urethral obstruction